The Challenging Process of Developing an Antenatal Social Intervention for Parents From Culturally Diverse Backgrounds to Reduce Postnatal Distress: A Participatory Action Research Study - Sophie Isobel; Kahala Dixon; Alison Tutt; Bridget Clay; Sylvia Lim‐Gibson (Health Expectations)
ABSTRACT Background A lack of social support contributes to women from culturally diverse backgrounds experiencing higher rates of perinatal distress and lower rates of service engagement. Objective/Methods This participatory action research study aimed to understand what a culturally appropriate social intervention may look like for pregnant women from culturally diverse backgrounds. Field notes and qualitative transcripts were descriptively synthesised. Results Challenges of engaging with culturally diverse communities in the context of perinatal health services were identified. Cultural factors and practices were seen to impact upon service engagement, with parents more likely to seek support outside of health settings. Community members expressed frustrations with the lack of deep cultural sensitivity in the structure and delivery of health services. Clear definitions in scope and aim of any intervention were indicated, before further community engagement. Discussion Challenges in engaging individuals and services from diverse communities highlighted the risks of ideas embedded in oversimplified understandings based on cultural stereotypes and assumptions of homogeneity of experiences at the intersection of cultural diversity, perinatal distress and health services. Conclusions Deep cultural sensitivity requires an understanding of how members of population groups perceive and understand health and wellbeing to directly inform the development of any intervention. Attempting to design a culturally sensitive intervention for socially isolated and culturally diverse parents within mainstream health services, led to a paradoxical tension between attempting to address needs in culturally insensitive ways or not attempting to address the needs at all. Patient or Public Contribution Members of the public and people who identified as having lived experience of social isolation, cultural diversity or mental distress were engaged in the community consultation phase of the study.